2019
DOI: 10.1097/md.0000000000017020
|View full text |Cite
|
Sign up to set email alerts
|

Are heart doses associated with survival in patients with non-small cell lung cancer who received post-operative thoracic radiotherapy?

Abstract: The aim of this retrospective national cohort study is to assess the association between various radiation heart dosimetric parameters (RHDPs), acute myocardial infarct (AMI) and overall survival (OS) outcomes in non-small cell lung cancer (NSCLC) patients treated with post-operative thoracic radiotherapy (PORT) using contemporary radiation techniques.We identified patients with stage I to III NSCLC treated with PORT at the 2 national cancer institutions from 2007 to 2014. We linked their electronic medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…One study concluded that heart doses were not associated with OS (heart V50: HR, 1.01; P = .868); however, the small sample size (43 cases) limited the statistical power. 14 The other study included 284 cases and found a strong correlation between increasing heart dose and OS; however, this study included 55 patients (19.4%) with R1 resection, nonuniform stages (I-III), and a heterogeneous radiation dose (45-70 Gy). 15 Patients who underwent R1 resection had poor survival and tended to receive a high administrative dose, suggesting R1 resection may confound the relationship between the heart dose and OS.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One study concluded that heart doses were not associated with OS (heart V50: HR, 1.01; P = .868); however, the small sample size (43 cases) limited the statistical power. 14 The other study included 284 cases and found a strong correlation between increasing heart dose and OS; however, this study included 55 patients (19.4%) with R1 resection, nonuniform stages (I-III), and a heterogeneous radiation dose (45-70 Gy). 15 Patients who underwent R1 resection had poor survival and tended to receive a high administrative dose, suggesting R1 resection may confound the relationship between the heart dose and OS.…”
Section: Discussionmentioning
confidence: 92%
“… 11 , 12 , 13 Moreover, to our knowledge, only 2 studies have investigated whether the heart dose in PORT affects OS. One study had a limited sample size of 43 patients, 14 and the other had 289 patients but included patients with incomplete resection (R1) who had nonuniform stages (I-III), and it used a heterogeneous radiation dose (45-70 Gy). 15 Therefore, the conclusions were not convincing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 , 22 ] However, it was reported that radiation heart dosimetric parameters were not associated with OS. [ 23 ] In support of this hypothesis, a meta-analysis was conducted based on modern PORT. [ 11 ] The results reported modern PORT could decrease local recurrences and increase OS in patients with stage pIIIA-N2 NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…29 Finally, a small national-level cohort study investigated radiation PORT for pN2 NSCLC e12 -Clinical Lung Cancer January 2021 heart dose parameters in patients receiving PORT for N2 or margin-positive disease and found no association with OS. 30 In contrast to the SEER databases, the National Cancer Database (NCDB) has comprehensive baseline characteristics and treatmentrelated details, including receipt of chemotherapy. Multiple NCDB analyses have demonstrated a benefit of PORT for pN2 disease.…”
Section: Nikhil P Mankuzhy Et Almentioning
confidence: 99%